Disaster Recovery Plan Analysis Based on the NIST SP 800-34 Framework (Case Study: PT Wijaya Karya (Persero) Tbk.) - Dwi Pamungkas, Eric; Fatonah, Nenden Siti; Firmansyah, Gerry; Akbar, Habibullah (Jurnal Indonesia Sosial Sains, 2023)
PT Wijaya Karya (Persero) Tbk. (WIKA) is a state-owned company engaged in the construction sector and EPC is currently developing its business in the mining and investment sectors both at home and abroad. Information Technology is one of the supports to achieve its goals. The use of Information Technology is urgently needed by WIKA in order to increase the effectiveness and efficiency of the company's operational activities. In this regard, it is necessary to develop procedures for managing information technology resources to support WIKA's business continuity, which includes services for internal or external users. In the use of information technology, the Disaster Recovery Plan (DRP) is an important part of IT services in efforts to prevent Data Center Fail-Over caused by disasters. With the DRP procedure, it is expected that the Information Systems Bureau as the manager of WIKA's information technology can immediately anticipate if a Disturbance or Disaster occurs that has the potential to disrupt a large number (the majority) of processes or activities that are very critical for business continuity. This Disaster Recovery Plan is guided by the NIST SP 800-34 framework which begins with identifying and assessing risk, Business Impact Analysis (BIA), identification of preventive controls and preparation of contingency strategies.